العنف الاسري والمرأة العاملة دراسة ميدانية في مدينة الديوانية - محمد, انيس شهيد (lark, 2019)
Abstract:The present study deals with a very important issue concerning the family, which is the first structure in the society, namely the violence directed at women by the members of their family towards it, namely the working woman who introduced herself in a difficult life in an unjust and inequitable society that sacrificed and sacrificed for the happiness of her family , And despite the seriousness of this phenomenon on the community and the family in particular, but we note the increase in recent times in all communities, especially the Iraqi society due to the conditions experienced by the security breaches and violations of the law and non-respect, and in order to achieve the basic objectives of the current study has been selected The sample is composed of (120) respondents to measure family violence directed against working women. This study is an analytical descriptive study. In this study, the social survey method was used. The questionnaire was used to obtain data. (20-30 years) are the most age group exposed to domestic violence. Most of the educational groups are exposed to university degrees. The female respondents are found to be more vulnerable to domestic violence. Most of the educational groups are subjected to violence by university degree holders , And Ghaleb The economic factor plays an important role in the perpetration of violence against women within the family and the economic abuse of women. Economic abuse has been shown to play an important role in the perpetration of violence against women within the family, The multiplicity of forms of violence faced by women is physical and moral violence, physical violence is the beating is one of the most important forms of violence towards the wife, followed by moral violence represented in irony, betrayal and abandonment.